Perspectiva tridimensional no realismo jurídico - Cavalcanti, Rodrigo de Camargo (2010)
This work aims to bring a perspective about law that underlies smoldering in life itself, lived by the sentient ever-changing beings, entering, mainly, in the lessons of García Maynez and his three circles theory, that will alow us to evoque the integrity fo law in all its strands privileging, in this work, the reading of Gunther Teubner and his legal realism, with the critical conception of compassionate view of Theodor Adorno, and Deleuze and his ritornello, aways with the solid and capital ground of the Humanistic Capitalism´s Theory, essencialy in its jushumanistic principality, according was brilliantly conceived by Ricardo Hasson Sayeg. For this, the Triad makes presence in the whole text in many ways: validity, applicability and effectiveness, freedom, equality and fraternity, text, metatext and intratext; territorialization, deterritorialization, and reterritorialization; past, present and future. Aways for the densification, Walking in a spiral, away from a linear historical meaning of law, but in order of consideration of the "minor literature" that permeates society and that is urgent in the relevance of the application of law and its role as a promoter of a creative freedom, overly human